Te⋯N secondary-bonding interactions in tellurium crystals: Supramolecular aggregation patterns and a comparison with their lighter congeners - Tiekink, Edward R. T. * (Elsevier, 2022)
Supramolecular aggregation patterns featuring Te…N secondary-bonding interactions have been identified in the crystals of tellurium(II) and tellurium(IV) compounds through a survey of the Cambridge Structural Database; 77% of examples involve tellurium(II) centres. The presence of Te…N secondary-bonding interactions has been established in approximately 11% of crystals having molecules containing tellurium and nitrogen atoms. Of the 148 Te…N contacts identified in the survey, the overwhelming majority can be classified in terms of chalcogen-bonding invoking the σ-hole bonding concept; there are five examples of π-hole interactions. Of the aggregates featuring Te…N interactions, just over half occur within one-dimensional architectures, being chains or tapes, over a third occur with zero-dimensional aggregates with 11 examples of two-dimensional arrays and one three-dimensional architecture. While in most aggregates the tellurium atom participated in a single Te…N interaction only, a sizeable minority (24%) featured tellurium forming two interactions. Certain classes of molecules exhibited very high propensities to form Te…N interactions: [1,3]tellurazolo[5,4-b]pyridines (80%), 2,1,3-benzotelluradiazoles (75%) and 1,3-benzotellurazoles (80%). Compared to the supramolecular association in crystals featuring 2 Se…N interactions, Te…N interactions are more likely to form, have relatively shorter Te…N distances and tend to form higher-dimensional aggregates, all observations consistent with the greater polarizability of the tellurium atom and the more pronounced σ-hole.